Ministry Of Finance Decree No. 188 of the Year 2022 Amending Certain Provisions of the Executive Regulations of the Uniform Tax Procedure Law Promulgated by Minister of Finance Decree No. 286 of the Year 2021 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic